Comparison between the Wheeler-Thanhauser Orchid Collection at Ball State University and the Orchid Collection Riyadh, Saudi Arabia - Alrasheed, Wafa (2015)
The beauty, complexity as well as the implausible diversity of the orchid flowers are unrivaled in the world. Orchids can be found in the equatorial tropics as well as the arctic tundra. The main logic behind the diversity of the orchid plants is in their ability to adapt to the environment normally located. There are numerous varieties of orchids that normally thrive in a wide range of different growing conditions, making it possible to find an orchid in almost any man-made environment as well. In this study, a comparison of orchids from two diverse collections was made utilizing printed materials (books and articles), and online database resources. The detailed analysis of the descriptive information of orchid genera with similar features between the two collections is presented. Thesis (M.A.) Department of Biology